A Comparative Study of Derrida’s Binary Opposition in Escher’s Day and Night - Mousavilar, Ashraf-o-Sadat; Pourmahmoud, Sadaf (Revista de Humanidades, 2021)
Resumen: Este estudio ha comparado la teoría de la oposición binaria de Derrida en “Dia y Noche” de Maurits Escher. Las oposiciones binarias son los principios dominantes del mundo material. Sin lugar a dudas, las oposiciones no pueden dejar de reflejarse en el arte humano, especialmente en las ilustraciones visuales. Para el estudio comparativo de la teoría de Derrida con las artes visuales, fue necesario elegir un indicador de trabajo artístico. Así, la pintura "Día y noche" fue seleccionada por Escher como la obra artística más opuesta de la época contemporánea, que muestra las funciones artísticas de la teoría en sintonía con las obras artísticas visuales. Esto se debe a que la forma y el contenido de este trabajo tienen abundantes oposiciones. Los resultados de este estudio, que se realiza mediante método comparativo y analítico, muestran que el número de oposiciones binarias en esta Pintura llega a 7 ítems e incluye contenido y oposición binaria narrativa y se puede ajustar con la teoría de Derrida en términos de generalización a funciones artísticas. Abstract: This article aimed at conducting a comparative study of Derrida’s binary oppositions theory in Maurits Escher’s Day and Night painting, indicating the applicability of the functions of the theory to the visual artistic works. Binary oppositions are among the dominant principles of the material world. Undoubtedly, such oppositions cannot be without their reflections in human art, especially visual illustrations. Sometimes, art reflects these oppositions and contradictions as they are and depicts them in the form of symbols and signs. For the sake of the comparative study of Derrida’s theory with visual arts, it was necessary to choose a seminal artistic work. Hence, the Day and Night painting by Escher was selected as the most opposing artistic work of the contemporary times. This is because the title, form, and content of this work have plenty of oppositions. The results of this study, conducted with the aid of comparative and analytical methods, show that the number of binary oppositions in this Painting reaches to 7 items. In terms of generalization to artistic functions, this includes form and performance (content and validity) binary oppositions, which are applicable to Derrida’s theory.